Membangun Kepemimpinan Transformatif : Strategi Motivasi, Pengambilan Keputusan dan Pengendalian Konflik Pada Pelatihan LKMM-TD - Wiratama, Dadang; Nataliawati, Rita; Alwi, Hadad (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore and analyze effective strategies in building leadership through motivational approaches, decision-making, and conflict management in Basic Student Leadership and Management Training (LKMM-TD) training. Using a descriptive qualitative approach, this study highlights the strategic role of training in improving transformational leadership capacity among students. The results of the study indicate that LKMM-TD training significantly contributes to the development of visionary, inspiring, and responsive leadership characters to team dynamics. Training participants are able to internalize motivational theories to mobilize individual and group potential, apply decision-making based on situational analysis effectively, and manage conflicts constructively in order to create harmonious working relationships. Thus, LKMM-TD has proven to be a strategic means in developing adaptive and transformative young leaders in the context of the organization.